PTU-225 Strategies to improve response rates to patient reported outcome measures in a surgical rct. (22nd June 2015) - Wood, J; Bruhn, H; Cook, JA; McDonald, A; Norrie, J; Watson, AJ
Abstract : Introduction: Difficulties achieving high response rates to patient reported outcome measures (PROMs) within clinical research are well recognised. The eTHoS trial, which compares Stapled Haemorrhoidopexy with Traditional Haemorrhoidectomy for the treatment of grade II-IV haemorrhoids, is no exception. Early response rates to postal PROMs on quality of life (distributed at 12 and 24 months post-randomisation) showed that their return was respectively only 67% (112/166) and 45% (5/11). Monetary incentives may improve such responses. 1 High value incentives may have a greater overall effect than lower value incentives, 2 however evidence from RCTs is limited. We examined whether introducing monetary incentives affected response rates from subsequent postal PROMs in a subset of the eTHoS cohort. Method: Two studies were conducted. In the first (which began in June 2013), participants (n = 326) were randomly allocated to one of 4 groups: 1) no incentive; 2) £5 gift voucher enclosed with 12 and 24 month questionnaires; 3) £5 gift voucher at 12 months only; 4) £5 gift voucher at 24 months only. In the second, participants are sent a £30 gift voucher on receipt of completed questionnaires (12 and /or 24 months). This study began in October 2014 and is expected to run until end of eTHoS follow up (June 2016). At the time of study design (July 2014), the 24 month postal PROMs response rate was 60% (with 440 patients yet to reach 24 months). Primary analyses for our first study examined effects of a £5 gift voucher incentive at 12 and/or 24 months on response rates to postal PROMs. A secondary analysis will examine a non-randomised comparison on response rates of incentives vs. no incentives. For study 2, primary analyses will examine the effect of a £30 gift voucher at 12 and/or 24 months on questionnaire response rates. The trial team also employed traditional methods in an attempt to improve postal response rates including implementing a shortened reminder questionnaire, database provision to allow participants to complete questionnaires online, and administering a study newsletter one week before the 12 and 24 month PROMs were due. Results: Study1 ceased in October 2014 as there appeared to be little benefit; response rates at 12 months remained lower than expected, 77% (267/347) and at 24 months, 66% (75/113). Conclusion: Further data showing secondary analysis results and preliminary outcomes from our second study will be presented (strategies employed in the eTHoS trial which aimed to boost response rates will be discussed). Disclosure of interest: None Declared. References: Edwards PJ, et al . Cochrane Database of Syst Rev 2009:MR000008 Brueton V, et al . Cochrane Database Syst Rev 2013:MR000032